2016
DOI: 10.1007/s00134-016-4303-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics on the incidence of ventilator-associated pneumonia in critically ill patients: a randomized controlled multicenter trial

Abstract: Therapy with the probiotic bacteria B. Subtilis and E. faecalis are an effective and safe means for preventing VAP and the acquisition of PPMO colonization in the stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
142
3
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(164 citation statements)
references
References 39 publications
4
142
3
9
Order By: Relevance
“…In 2016, a randomized, multi-center study examined the use of probiotics containing live Bacillus subtilis and Enterococcus faecalis via nasogastric tube in ventilated patients. Patients receiving probiotic therapy had a statistically significant reduction in the rate of ventilator associated pneumonia compared to those that did not (36.4 to 50.4%, p=0.031) (108). Ultimately, however, well designed trials are still required prior to wider adoption of probiotics in the intensive care unit.…”
Section: Treatment Targeting the Microbiomementioning
confidence: 99%
“…In 2016, a randomized, multi-center study examined the use of probiotics containing live Bacillus subtilis and Enterococcus faecalis via nasogastric tube in ventilated patients. Patients receiving probiotic therapy had a statistically significant reduction in the rate of ventilator associated pneumonia compared to those that did not (36.4 to 50.4%, p=0.031) (108). Ultimately, however, well designed trials are still required prior to wider adoption of probiotics in the intensive care unit.…”
Section: Treatment Targeting the Microbiomementioning
confidence: 99%
“…In addition, the authors show that the mean time to developing a VAP was significantly longer in the probiotic group vs the control group (10.4 vs 7.5 days, respectively; P = .022). Finally, this trial demonstrated a lower incidence of gastric colonization by pathogens in the probiotic arm ( P = .004) 12 . Currently, other trials such as the Prevention of Severe Pneumonia and Endotracheal Colonization Trial (PROSPECT, NCT0178275511) are evaluating the preventive effects of probiotics on VAP and other infectious complications in the critically ill 13 …”
mentioning
confidence: 78%
“…Thus, the results of this meta‐analysis do not provide sufficient evidence on the efficacy of probiotic therapy in the prevention of VAP in the ICU 11 . Recently, Zeng et al, 12 in a well‐performed study including 235 critically ill adult patients who were expected to be in mechanical ventilation for >48 hours, safely administered 2 strains of living bacteria ( Bacteroides subtilis and Enterococcus faecalis ). The authors demonstrated that probiotic therapy is associated with a significant reduction in the incidence of VAP (36.4% vs 50.4 %, P = .031, in the probiotic and control groups, respectively).…”
mentioning
confidence: 89%
“…This might shed light on our understanding of the conflicting results with the effect of probiotics on the incidence of VAP in critically ill patients. In an open-label, multicenter randomized controlled trial involving 235 critically ill adult patients, therapy with the probiotic bacteria Bacillus subtilis and Enterococcus faecalis were found to be effective and safe for preventing VAP and the acquisition of multidrugresistant pathogen (MDR) colonization [17].…”
Section: Icu-acquired Infectionsmentioning
confidence: 99%